2020
DOI: 10.1556/2006.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

How have excessive electronics devices and Internet uses been concerned? Implications for global research agenda from a bibliometric analysis

Abstract: Background and aimsExcessive use of electronic devices has become a major global problem. However, little is known about the development and current landscape of research concerning this field. This study aimed at exploring the overall publication trend and topics of research on the overuse of electronic devices and the Internet from 1971 to 2017.MethodsWe systematically searched the Web of Science (WoS) and Scopus databases for published articles on the excessive use of electronic devices and the Internet. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 85 publications
(92 reference statements)
1
7
0
Order By: Relevance
“…Firstly, we observe that Asian countries are less productive in gambling and more productive in ITC and gaming. This interest was also observed in the literature ( Chia et al, 2020 , Tran et al, 2020 ). More specifically, it was observed that ITC and gaming have received special attention in Southeast Asia being considered both in China and South Korea as national health problems ( Kuss et al, 2021 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Firstly, we observe that Asian countries are less productive in gambling and more productive in ITC and gaming. This interest was also observed in the literature ( Chia et al, 2020 , Tran et al, 2020 ). More specifically, it was observed that ITC and gaming have received special attention in Southeast Asia being considered both in China and South Korea as national health problems ( Kuss et al, 2021 ).…”
Section: Discussionsupporting
confidence: 73%
“…These studies use easy-to-understand production, collaboration, and impact indicators to identify trends over time. In the field of behavioral addictions, some studies have focused only on a particular behavioral addiction, such as internet use disorder ( Moreno-Guerrero et al, 2020 , Tran et al, 2020 , Vega-Almeida and Arencibia-Jorge, 2019 ), gambling and gaming ( Shaffer et al, 2006 , Stehmann, 2020 ) or a combination of the internet and gaming ( Carbonell et al, 2009 ). In the case of the analysis by country, the trend is the same, and studies focused only on a specific behavioral addiction ( Moreno-Guerrero et al, 2020 , Tran et al, 2020 , Vega-Almeida and Arencibia-Jorge, 2019 ) or those that involved the use of technologies and the internet ( Carbonell et al, 2009 ) were found.…”
Section: Introductionmentioning
confidence: 99%
“…Research on technostress undoubtedly requires greater post-disciplinary collaboration between researchers from both knowledge branches to collaborate closely, complementing each other in addressing holistic studies on the problems and challenges to be faced in the immediate future [99]. This is new when compared to recent bibliometric studies on the use of technology and its effects on mental health, where journals focus mainly on health issues (Psych* and Neuro*) [100].…”
Section: Discussionmentioning
confidence: 99%
“…The effects were more on young children than other age cohorts. 7 According to the US Centers for Disease Control and Prevention, an average child spends about 8 hours a day watching electronic screens. 8 Too much screen time and lack of sleep can lead to lack of productivity among children.…”
Section: Introductionmentioning
confidence: 99%